O uso da homeopatia popular no cuidado ao idoso em uma instituição de longa permanência - Cervi, Mariza Casagrande (2013)
Homeopathy currently represents, in Brazil, a medical, pharmaceutical and veterinarian specialty. However, its practice by non-doctors has been culturally accepted in health services for the population, belonging to the national scenery since the Empire times. It is responsible for an accessible and resolutive service, usually directed to a deprived and unaided population. Its background comes forward with a strong religious involvement. The object of this study is a Long-Stay Institution for the Elderly (ILPI), managed by a religious woman who utilizes complementary practices in the elderly health care, featuring the use of popular homeopathy. The research project has been submitted and approved by the Research Ethics Committee from the University of Passo Fundo, under the protocol number 440/2011. This is a single and investigative case study of a current phenomenon, in a real and daily life context, which aims to acknowledge the practice of popular homeopathy in the referred institute. The results contain the description of the effectiveness of this therapeutics, which empirically follows the Hahnemannian principles. The study has allowed recognizing the practice of popular homeopathy by non-doctors, as well as the perception from the professionals who work in the institution concerning this form of health service, considered as a punctual initiative, not thoroughly comprehended by the majority of the professionals.